An Ultra-Sensitive Colorimetric Sensing Platform for Simultaneous Detection of Moxifloxacin/Ciprofloxacin and Cr(III) Ions Based on Ammonium Thioglycolate Functionalized Gold Nanoparticles - Lihua Zhang; Jiang Li; Juan Wang; Xu Yan; Jinping Song; Feng Feng (Sensors)
Water pollution by antibiotics and heavy metals threatens the ecological environment and human health globally, yet there is no rapid method to detect multiple antibiotics and metal ions simultaneously. A simple, fast, and ultra-sensitive colorimetric chemosensor for the simultaneous detection of moxifloxacin (MOX), ciprofloxacin (CIP), and Cr(III) based on the aggregation of ammonium thioglycolate (ATG)-functionalized gold nanoparticles (ATG-AuNPs) was developed. Following the addition of MOX, CIP, and Cr(III), a color change in the solution was observed from wine-red to blue-grey. The UV–Vis signal of the ATG-AuNPs system blended with MOX, CIP, and Cr(III) in the range of 0~200 µM, 0~100 µM, and 0~5 µM was assessed and measured with detection limits (LODs) of 1.57 µM, 1.30 µM, and 57.1 nM calculated by 3σ/S, respectively. Therefore, this system has the potential to act as an effective colorimetric chemosensor for simultaneously detecting MOX, CIP, and Cr(III) in complex environmental systems.